Ways to Develop Mental Abilities in Preschool Children - Choriyeva Surayyo Choriyevna (Genius Journals, 2022)
This article talks about the development of intellectual abilities and skills, one of the tasks of mental education for the development of mental abilities in children of preschool age.
Keywords: preschool education; mental ability; mental development